Multi-particle impact behavior of Cu nanoparticles: A molecular dynamics investigation - Che Zhang; Zhou Li; Jiaqing Li; Peng Gao; Rui Wang; Chunyang Xia; Guanyu Deng (Next Materials)
While the single-particle impact model is widely used in studying the high-velocity impact behavior of particles, its scope is limited to the interaction between an individual particle and the substrate. In this work, a multi-particle molecular dynamics model was established to investigate the impact behavior of Cu nanoparticles and the surface quality of coatings. It was found that with the increase in particles' impact velocity from 100 m/s to 1500 m/s, three distinct coating structures can be identified: adhesion between nanoparticles, co-deformation, and liquefaction. Due to the anisotropy of plastic deformation, coatings formed by particles with the initial orientation [110] displayed the roughest surface, while those aligned with [111] and [001] exhibited smoother surfaces. Additionally, as nanoscale particles possess limited kinetic energy, it is difficult to create a large crater on the surface of the substrate. Therefore, it was necessary to elevate the temperature to soften the substrate, which can increase the crater depth and improve bonding quality. A successful approach to enhancing the bonding strength and surface quality of coatings involves simultaneous optimization of impact velocity, crystallographic orientation of particles, and substrate temperature.